Effect of pruning young branches on fruit and seed set in cassava - Pineda, Marcela; Yu, Benchi; Tian, Yinong; Morante, Nelson; Salazar, Sara S.V.; Hyde, Peter T.; Setter, Tim L.; Ceballos, Hernán (Frontiers Media, 2020)
Flowering in cassava is closely linked with branching. Early-flowering genotypes branch low and abundantly. Although farmers prefer late flowering genotypes because of their erect plant architecture, their usefulness as progenitors in breeding is limited by their low seed production. In general, the first inflorescence aborts in cassava. Preventing this abortion would result in early production of seeds and make cassava breeding more efficient. The objective of this study was to assess if pruning young branches prevents the abortion of first inflorescences and promotes early fruit and seed set. Four genotypes with early, late, very late, and no flowering habits were grown under an extended photoperiod (EP) or normal dark night conditions (DN). Additional treatments included pruning young branches at the first or second flowering event and spraying (or not) benzyladenine (BA) after pruning. One genotype failed to flower and was not considered further. For the remaining genotypes, EP proved crucial to induce an earlier flowering, which is a pre-requisite for pruning. Total production of seeds in EP plots was 2,971 versus 150 in DN plots. For plants grown under EP, the average number of seeds per plant without pruning was 3.88, whereas those pruned produced 17.60 seeds per plant. Pruning at the first branching event led to higher number of seeds per plant (26.25) than pruning at the second flowering event (8.95). In general, applying BA was beneficial (38.52 and 13.98 seeds/plant with or without spraying it, respectively). The best combination of treatments was different for each genotype. Pruning young branches and applying BA in the first flowering event not only prevented the abortion of inflorescences but also induced the feminization of male flowers into hermaphrodite or female-only flowers. The procedures suggested from this study (combining EP, pruning young branches, and spraying BA), allowed the production of a high number of seeds from erect cassava genotypes in a short period. The implementation of these procedures will improve the breeding efficiency in cassava.